2014
DOI: 10.1039/c3cc47747a
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing vitamin D3by conformationally selective co-crystallization

Abstract: A four-membered square-shaped H-bonding structure was successfully designed to synthesize vitamin D3 co-crystals. The co-crystallization process was found to be conformationally selective to result in topochemically stable materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 24 publications
0
72
0
Order By: Relevance
“…The possibility of alteration of the physicochemical properties after successful cocrystallization is especially welcomed in the case of active pharmaceutical ingredients (API). There are many examples of significant improvements of API behaviors both in vivo and in vitro [14,15] due to enhancement of pharmacokinetic properties as solubility [4,16,17] and bioavailability [18][19][20]. Also many other physicochemical properties can be modulated by cocrystallization including stability [21][22][23][24], hygroscopicity [25] and prolonged shelf life [26].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of alteration of the physicochemical properties after successful cocrystallization is especially welcomed in the case of active pharmaceutical ingredients (API). There are many examples of significant improvements of API behaviors both in vivo and in vitro [14,15] due to enhancement of pharmacokinetic properties as solubility [4,16,17] and bioavailability [18][19][20]. Also many other physicochemical properties can be modulated by cocrystallization including stability [21][22][23][24], hygroscopicity [25] and prolonged shelf life [26].…”
Section: Introductionmentioning
confidence: 99%
“…In the solution and in the solid state, the degree of freedom may be to some extent limited due to the demands imposed by the formation of pseudo-homodimers. For example, for the orthorhombic form it was shown that the two conformers are alternately connected by a set of intermolecular O -H O -H interactions to form a one-dimensional chain arrangement [Wang, Chun, Yu, & Mei, 2014].…”
Section: Resultsmentioning
confidence: 99%
“…In a recent structural studies (Wang, Zho, Qihui, & Mei, 2016), the hexagonal cell was proposed with the parameters given as a = b = 28.280Å and c = 5.932Å. The analysis of crystal structure data allowed suggesting that this polymorph contains exclusively α-chair conformation which is much prone to photo-or thermo-induced cyclization reactions than β conformer, and consequently it is more promising from the biochemical point of view (Wang, Chun, Yu, & Mei., 2014;). It should be born in mind that the value of the R factor that characterizes these investigations is of moderate accuracy, that is, 6.42 and 8.70%, respectively, and quite high even for large molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal stability can be signifi cantly improved by the addition of auxiliary components, excipients, which can very effectively protect vitamins from thermal decomposition. Further more, the selection of a suitable carrier in order to increase the thermal stability is a very topical issue (Sazan et al 2013, Corvis et al 2013, Li et al 1998, Wang et al 2013. One of the most reliable way to get an insight into the thermal stability of the preparation, is a method of thermal analysis (Brown et al 1998, Brown 1980.…”
Section: Introductionmentioning
confidence: 99%